Platelet-rich plasma in the management of Asherman's syndrome: An RCT - Atiyeh Javaheri; Katayoon Kianfar; Soheila Pourmasumi; Maryam Eftekhar (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Asherman's syndrome (AS) is a rare reproductive abnormality, resulting in endometrial collapse due to aggressive or recurrent endometritis and/or curettage.Objective: We aimed to assess the effectiveness of using platelet-rich plasma (PRP) to lower the recurrence rate of intrauterine adhesions (IUAs) following hysteroscopy.Materials and Methods: In this non-randomized clinical trial, women aged 20-45 years with AS diagnosed by sonohysterography, 3D sonography, hysteroscopy, or uterosalpingography between May 2018 and September 2018 were included. Participants (n = 30) were divided into case and control groups. Following hysteroscopic adhesiolysis, a Foley catheter was placed into the uterine cavity in all women. After two days, the catheter was removed, and 1-mL PRP was injected into the uterine cavity of women in the PRP (case) group, while the control received no PRP. All controls and subjects underwent diagnostic hysteroscopy 8-10 weeks following the intervention to assess the IUAs according to the American Society for Reproductive Medicine scoring system.Results: Our results did not reveal any significant difference in the menstrual pattern of either the control or test groups before or after treatment (p = 0.2). Moreover, the IUA stage in both studied groups before and after treatment was similar (p = 0.2). The duration of menstrual bleeding in both studied groups before and after treatment was also similar.Conclusion: PRP cannot change the menstrual pattern or development of postsurgical AS, as evaluated by follow-up hysteroscopy.